Study of platelet parameters in bacterial infections of lower respiratory tract - Dr. B Lakshmi Durga Srujana; Dr. Sushma Yalavarthi; Dr. Vasudha CL (Tropical Journal of Pathology and Microbiology, 2018)
Background: Respiratory tract infections are one of the commonest bacterial infections. Platelets play an important role in inflammatory response against infectious agents. Bacterial components activate platelets to release inflammatory mediators. The changes platelets undergo during their activation are reflected in the platelet parameters. This study aims to evaluate platelet parameters in the lower respiratory tract infections. Materials & methods: Cross-sectional study on sputum culture proven bacterial infections of the lower respiratory tract was done for three months. Platelet parameters of 94 cases were compared with 94 healthy controls. Cases were sub grouped as group A (with leucocytosis) and group B (without leukocytosis). Comparative analysis of platelet parameters between these subgroups and controls was done. P value was calculated and <0.05 was considered significant. Results: Platelet count (p <0.05) and plateletcrit were higher, Mean platelet volume (p <0.05), Platelet distribution width (p <0.001) and Platelet large cell ratio were lower in cases compared to controls. Group A showed significantly higher PLT (p < 0.05) and PCT (p <0.001) than group B whereas the difference in other parameters was not significant. All platelet parameters were significantly altered in patients with leukocytosis on comparison with controls whereas only MPV, PDW and P-LCR showed significant change in patients without leukocytosis when compared with controls. Conclusion: Platelet parameters show variation in the lower respiratory tract infections. As they can be determined as a part of routine complete blood picture analysis, they may be considered as markers of inflammation in the diagnosis of lower respiratory tract infections.